Corfu Crisis of 1923: Occupation of Kerkyra in Context of Italian Policy in Eastern Mediterranean - T. P. Nesterova (Научный диалог, 2019)
The history of the Italian occupation of the island of Kerkyra (Corfu), one of the Ionian Islands currently part of Greece, is considered. The period after 1912 when Italy, having won a military victory over the Ottoman Empire, occupied Libya and the Dodecanese Islands is characterized. It is noted that at this time another goal of Italian foreign policy in the Mediterranean was Albania, independence of which was proclaimed in 1912, and the adjacent Islands of the Ionian archipelago. The author of the article dwells on the fact that the signing of the Treaty of Lausanne of 1923, which finally secured the possession of the Dodecanese Islands for Italy, allowed Italy to intensify its policy in the Ionian sea region. The author was able to identify the main stages of the diplomatic struggle over the occupation of the island of Corfu, to show the special interest of Italy in resolving the issue of Corfu outside the structures of the new international organization - the League of Nations. It is proved that the final withdrawal of Italian troops from the occupied island was the result of negotiations between Italy, Britain and France, while the opinion of Greece was practically not taken into account. The article is based on Italian and British official publications of diplomatic documents.